ANALISIS INDEKS JALUR STABILITAS PADA KAPAL DI PERAIRAN DALAM - Anindita Utamidewi, (2023)
To evaluate the performance of maneuvers on ships can be done using numerical simulations using mathematical models. To carry out numerical simulations so far, the MMG model is often used to simulate ship maneuvers. A ship must be able to respond quickly to various maneuvers on the ship. When the ship experiences disturbance during sailing, such as avoiding other ships, coral reefs, and others. To be able to see the ship's maneuverability when avoiding disturbances, it can be done by looking for the stability path index value. To predict the ship's maneuverability, there are aspects that must be considered, namely the loading condition. Ships in general are not only operated in a fully loaded condition, but also in a half full or ballast condition so that the manuver characteristics are also influenced by the loading conditions. In this study, the calculation of the course stability index will be carried out on ships in three loading conditions, namely full loaded, half loaded, and ballast conditions. From the research results, when the conditions of full loaded, half loaded, and ballast ships have unstable maneuverability